2021
DOI: 10.3390/cancers13040671
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of the New Combined Hemo-Eosinophil Inflammation Index (HEI Index): A Multicenter Analysis of Anal Cancer Patients Treated with Concurrent Chemo-Radiation

Abstract: Anal squamous cell carcinoma (SCC) is a rare tumor, and bio-humoral predictors of response to chemo-radiation (CT-RT) are lacking. We developed a prognostic score system based on laboratory inflammation parameters. We investigated the correlation between baseline clinical and laboratory variables and disease-free (DFS) and overall (OS) survival in anal SCC patients treated with CT-RT in five institutions. The bio-humoral parameters of significance were included in a new scoring system, which was tested with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Nevertheless, the combined influence of these parameters on outcome have not been assessed. Other composite blood based markers that have been reported to be associated with impaired prognosis are the systemic inflammatory index consisting of platelets, neutrophils and lymphocytes and the Hemo-Eosinophil-Inflammatory index consisting of hemoglobin and eosinophil levels [24,25].…”
mentioning
confidence: 99%
“…Nevertheless, the combined influence of these parameters on outcome have not been assessed. Other composite blood based markers that have been reported to be associated with impaired prognosis are the systemic inflammatory index consisting of platelets, neutrophils and lymphocytes and the Hemo-Eosinophil-Inflammatory index consisting of hemoglobin and eosinophil levels [24,25].…”
mentioning
confidence: 99%
“…Biomarkers and patient-reported outcomes also emerged as recent trend topics in ASCC. The HPV/p16 status, tumor-infiltrating lymphocytes (TILs) rate, Epidermal Growth Factor Receptor (EGFR) overexpression, circulating HPV-DNA and blood biomarkers [Neutrophil-to-lymphocyte ratio (NLR), Systemic Index of Inflammation (SII), absolute number of leukocytes and neutrophils, hemoglobin level] were the most frequently studied biomarkers [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that peripheral blood leukocytosis and neutrophilia re ected cancerrelated in ammation and has been proposed as prognostic immunological biomarkers for various malignancies 11,21 . A study validated leukocytosis as an independent prognostic factor in CRC, which provided for the rst-time vital insight on the correlation of peripheral pretreatment leukocytosis with the tumor-in ltrating cells contexture and might be relevant for future risk strati cation 22 .…”
Section: Discussionmentioning
confidence: 99%